Loading of vitamin D2 in native and modified sodium caseinate: Delineation of physico-chemical and in-vitro bioaccessibility attributes. (1st February 2022) - Syama, M.A.; Arora, Sumit; Gupta, Chitra; Singh, A.K.
Abstract: Search for a suitable carrier for vitamin D2 delivery was carried out with both native sodium caseinate (NaCas) and modified NaCas i.e. succinylated sodium caseinate (SNaCas), reassembled sodium caseinate (RNaCas) and reassembled succinylated sodium caseinate (RSNaCas). The possible interaction behind the loading of vitamin D2 in native and modified NaCas was elucidated by analysing the different physico-chemical attributes of protein and protein-vitamin D2 complexes. The results were also helpful in confirming the loading of vitamin D2 in native and modified NaCas. A significant increase (p < 0.05) was observed in particle size and zeta potential of native and modified NaCas upon loading of vitamin D2. Microstructural analysis revealed vitamin D2 loading does not alter the surface morphology of native and modified NaCas. Tryptophan fluorescence intensity studies of vitamin D2 loaded native and modified NaCas showed red shift in wavelength maxima which indicates a slight increase in the hydrophobicity of the molecule. Loading of vitamin D2 on protein reduces the tryptophan intensity which indicates that hydrophobic interaction is responsible for binding of vitamin D2 with native and modified NaCas. In-vitro bioaccessibility of vitamin D2 was significantly increased (p < 0.05) when loaded in native and modified NaCas. Highlights: Vitamin D2 was loaded on native and modified NaCas by different methods. Loading of vitamin D2 in milk protein increased the particle size and zeta potential. Tryptophan intensities confirm the structural modification in milk protein. Complex formation have no influence on RP-HPLC elution profile. In-vitro bioaccessibility of free vitamin D2 was increased after loading in milk protein.